The efficacy of UVA1 phototherapy in psoriasis: Clinical and histological aspects - Narumol Silpa-archa (2020)
© 2019 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background: Although ultraviolet A1 (UVA1) phototherapy is available for nearly 30 years, only few studies have been conducted for plaque-type psoriasis. Objectives: To determine the efficacy and safety of UVA1 phototherapy in psoriasis by assessing the clinical and histological outcomes. Methods: This open study enrolled 15 patients with moderate to severe plaque-type psoriasis. All of the patients had skin type IV. A whole-body UVA1 device consisting of 24 lamps, was irradiated at a medium dose of 50 J/cm2 three-times weekly for 30 sessions. Topical and systemic psoriasis treatments were discontinued before and during treatment; patients could only use emollients and antihistamines until 1-month post-completion. Psoriasis Area and Severity Index (PASI) scores were determined at baseline; at sessions 10th, 20th and 30th; and 1 month after treatment. Four-millimetre punch biopsies were obtained from the same psoriasis lesion at baseline and session 30th. Changes in histopathological gradings and polymorphonuclear, lymphocyte and Langerhans cell numbers were monitored. Results: Twelve patients completed the study. The mean age was 41.3 years (range: 25-71). The median PASI scores at baseline, session 30th and 1-month post-treatment were 16 (8.2, 43.3), 11 (4.4, 43.3) and 9.2 (2.7, 36.4), respectively. Although the PASI scores had improved significantly by 1-month post-treatment (P =.006), the histological parameters demonstrated minimal changes. All patients tolerated the phototherapy well and the most common side effect was skin tanning. Conclusions: While medium-dose UVA1 phototherapy demonstrated some efficacy in moderate to severe plaque-type psoriasis. However, it might not be an excellent choice.